2018
DOI: 10.1111/1541-4337.12366
|View full text |Cite
|
Sign up to set email alerts
|

Design Elements of Listeria Environmental Monitoring Programs in Food Processing Facilities: A Scoping Review of Research and Guidance Materials

Abstract: Occurrence of Listeria monocytogenes (Lm), the causative agent of listeriosis, in food processing facilities presents considerable challenges to food producers and food safety authorities. Design of an effective, risk-based environmental monitoring (EM) program is essential for finding and eliminating Lm from the processing environment to prevent product contamination. A scoping review was conducted to collate and synthesize available research and guidance materials on Listeria EM in food processing facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 72 publications
0
28
0
1
Order By: Relevance
“…The EMP consists of the collection of samples from food contact and nonfood contact surfaces of a food processing facility to detect Listeria contamination and verify the adequacy of control measures (Zoellner et al., 2018). As such, an EMP should be validated to assess its efficacy.…”
Section: Verification Of the Empmentioning
confidence: 99%
See 2 more Smart Citations
“…The EMP consists of the collection of samples from food contact and nonfood contact surfaces of a food processing facility to detect Listeria contamination and verify the adequacy of control measures (Zoellner et al., 2018). As such, an EMP should be validated to assess its efficacy.…”
Section: Verification Of the Empmentioning
confidence: 99%
“…As a general rule, regulatory agencies guide the design of an EMP on a risk‐based approach using factors such as the ability of the RTE food to support the growth of L. monocytogenes , the methods used to control postlethality step contamination, the likelihood of contamination, and the risk of being linked to human listeriosis (Zoellner, Ceres, Ghezzi‐Kopel, Wiedmann, & Ivanek, 2018). However, many international food safety authorities have different approaches with regard to EMPs for Listeria spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the validation sampling results demonstrate the importance of sampling by an outside party, which can increase confidence in results and also identify potentially problematic sampling schemes. It can also serve to periodically validate the efficacy of a routine Listeria environmental monitoring program (1,28). However, a single validation sampling may not necessarily be appropriate to assess routine sampling conducted over a preceding year; discrepancies between routine and validation sampling should be followed up by a more comprehensive sampling process review and, if deemed appropriate, a root cause analysis investigation (e.g., of the routine sampling procedures if the validation sampling provides considerably larger proportion of positive samples).…”
Section: Packinghousementioning
confidence: 99%
“…However, there is still a lack of research to support these guidance documents, as compared with other food sectors. A 2018 scoping review of research and guidance materials related to Listeria PEM programs revealed that, of 74 references relating to environmental monitoring, only four were related to the fresh produce sector, compared with 20 and 19 in the meat and dairy sectors, respectively (28).…”
mentioning
confidence: 99%